Critical rationalism and engineering: methodology. - Staples, Mark (Synthese, 2015)
Engineering deals with different problem situations than science, and theories in engineering are different to theories in science. So, the growth of knowledge in engineering is also different to that in science. Nonetheless, methodological issues in engineering epistemology can be explored by adapting frameworks already established in the philosophy of science. In this paper I use critical rationalism and Popper's three worlds framework to investigate error elimination and the growth of knowledge in engineering. I discuss engineering failure arising from the falsification of engineering theories, and present taxonomies of the sources of falsification and responses to falsification in engineering. From this I discuss contexts of research and design in engineering, ad hoc rescue of engineering theories, and engineering assurance.